Factors Affecting Taxpayer Compliance in Paying Land and Building Tax at Semarang City - Sempurna, Caesar Robin Vegi; Damajanti, Anita (Economics and Business Solutions Journal, 2023)
This study aims to examine the effect of attitudes, tax sanctions, and taxpayer awareness on the compliance of PBB taxpayers in Semarang City. Data were collected by questionnaire method given directly to respondents at PBB payment places. Respondents were selected by convenience sampling method, namely respondents who were willing to fill out the questionnaire. Respondents were asked to answer questions on the questionnaire related to the variables of taxpayer attitudes, taxpayer awareness, tax sanctions, and PBB taxpayer compliance. The number of respondents was set as 100 respondents. The questionnaires that were filled in for all question items were 80 questionnaires. 20 questionnaires could not be processed because they were not filled in. Data analysis was carried out with multiple linear regression models. This study found a positive influence of tax penalties on tax compliance, but no effect of taxpayer attitudes and taxpayer awareness on taxpayer compliance in Semarang city. The findings are expected to be taken into consideration by the Semarang City Government in making policies on PBB collection.Keywords: taxpayer attitude, tax sanctions, taxpayer awareness, taxpayer compliance